Prospek Ushatani pada Lahan Pesisir di Desa Pleret Kecamatan Panjatan, Kulon Progo - Ken Suratiyah; Tuti Wirdianingsih (Agro Ekonomi, 1999)
Farm on seaboard land is another alternative besides farm in wet fields.